Benign and malignant soft tissue tumours of the extremities: A histopathological review in a tertiary hospital in Sarawak - Mohammad Zulkarnaen, Ahmad Narihan; Dayangku Norlida, Awang Ojep; Yusri, Yusuf; Muhammad Zawawi, Zuhardi; Nur Syafiqah, Mohd Fazeri; Angelina, Allan; Maria Wee, Soo Ting (2025)
Soft tissue tumours (STTs) are neoplasms arising from non-epithelial, extra-skeletal connective tissues such as adipose tissue, muscle, fibrous tissue, and peripheral nerves. Clinicopathological analysis is crucial for achieving early and accurate diagnosis, particularly when multiple differential diagnoses are considered. To date, no study has examined the clinicopathological profile of extremity STTs in Sarawak.